2019
DOI: 10.30870/educhemia.v4i1.4867
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan PBL untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa pada Konsep Koloid

Abstract: Students' creative thinking skills are needed in chemistry learning, because some chemistry is contextual. Students' creative thinking skills in Indonesia tend to be low. This research aimed to improve students' creative thinking skills on the concept of colloids by implementing the PBL model. This research used the pre-experimental method with pretestposttest one group design. The sample in this research was all students in one class of XI IPA taken using purposive sampling method. The instrument was used con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
2
8
0
7
Order By: Relevance
“…", 80% of evaluative thinking skills are in the" Very Good "category. The research results obtained are reinforced by the results of previous research where the application of the PBL model can improve students' ability to give ideas, and analyze the problems given to the LKS very well (Herdiawan et al, 2019).…”
Section: Students' Creative Thinking Skills In Handling Fish Bone Wastesupporting
confidence: 63%
“…", 80% of evaluative thinking skills are in the" Very Good "category. The research results obtained are reinforced by the results of previous research where the application of the PBL model can improve students' ability to give ideas, and analyze the problems given to the LKS very well (Herdiawan et al, 2019).…”
Section: Students' Creative Thinking Skills In Handling Fish Bone Wastesupporting
confidence: 63%
“…Dirmanto, et al (2021) found that in the PBL class the percentage of students' scientific attitudes was much higher than in conventional classroom learning, as well as in terms of creativity and learning outcomes. Meanwhile, Nuswowati, et al (2017), Herdiawan, et al (2019 found that the application of the Problem Based Learning (PBL) model was able to improve students' creative thinking skills and creative actions.…”
Section: Resultsmentioning
confidence: 99%
“…Model pembelajaran sangat penting diterapkan guru dalam mecapai tujuan pembelajaran. Model pembelajaran adalah seluruh rangkaian penyajian materi ajar meliputi aspek sebelum, sedang, dan sesudah pengajaran yang dilakukan guru serta segala fasilitas yang terkait yang digunakan secara langsung dalam belajar (Ariani, 2020;Herdiawan et al, 2019;Widodo et al, 2020). Salah satu model yang dapat diterapkan adalah dengan penggunaan mulimedia pembelajaran di dalam proses pembelajaran (Admadja & Marpanaji, 2016;Sari & Sugiyarto, 2015;Surjono, 2017).…”
Section: Pendahuluanunclassified